2021
DOI: 10.1021/acsomega.0c05519
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Modeling of the Effects of Hydrated Lime (Calcium Hydroxide) as a Filler in Bituminous Materials

Abstract: Hydrated lime is widely used as a mineral filler to improve several properties of bituminous materials such as reducing the susceptibility of the composite to moisture-induced damage. Although experimental evidence supports the efficacy of using hydrated lime as a mineral filler, the molecular scale mechanism of reactivity of hydrated lime within the bitumen to reduce moisture damage is not understood. This is important when considering the durability of structural applications of bituminous materials such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…On the other hand, Al-Tameemi and Grajales et al, [10,11] found that slaked lime can react with some specific functional groups in the asphalt and form a strong waterproofing compound that significantly improves the water stability of the asphalt mixture. Likewise, Hu et al, [12][13][14][15] successfully used waste brake pads as fillers to modify the asphalt mixture and found satisfactory results with respect to enhancing both the moisture tolerance and high-temperature stability performance of the asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Al-Tameemi and Grajales et al, [10,11] found that slaked lime can react with some specific functional groups in the asphalt and form a strong waterproofing compound that significantly improves the water stability of the asphalt mixture. Likewise, Hu et al, [12][13][14][15] successfully used waste brake pads as fillers to modify the asphalt mixture and found satisfactory results with respect to enhancing both the moisture tolerance and high-temperature stability performance of the asphalt mixture.…”
Section: Introductionmentioning
confidence: 99%